Predictive Potential of Motivation to Learn in the use of Learning Strategies - Inácio, Amanda Lays Monteiro [UNESP]; Boruchovitch, Evely; de Brito Cunha, Neide; de Miranda, Lúcia do Rosário Cerqueira (FapUNIFESP (SciELO), 2023)
This paper investigates motivation to learn and learning strategies in a sample of 353 Brazilian students in elementary and secondary education. Data were collected through the Motivation to learn scale and two Learning Strategies Assessment Scales, one for elementary school and another for high school. Learning goals and use of metacognitive strategies were predominant in the sample. Significant positive and negative correlations between the subscales were found. Two models emerged explaining 33% and 37% of the variance in the use of learning strategies that can be attributed to motivation to learn factors. The study underscores the importance of motivation to learn for engaging students in strategic behavior.
Potencial Preditivo da Motivação para Aprender no Uso das Estratégias de Aprendizagem
Keywords: achievement goals; basic education; cognitive and metacognitive strategies; Self-regulation